Transitions between biomes are common and directional in Bombacoideae (Malvaceae). (26th February 2020) - Zizka, Alexander; Carvalho‐Sobrinho, Jefferson G.; Pennington, R. Toby; Queiroz, Luciano P.; Alcantara, Suzana; Baum, David A.; Bacon, Christine D.; Antonelli, Alexandre
Abstract: Aim: To quantify evolutionary transitions between tropical evergreen rain forest and seasonally dry biomes, to test whether biome transitions affect lineage diversification and to examine the robustness of these results to methodological choices. Location: The tropics. Time period: The Cenozoic. Major taxa studied: The plant subfamily Bombacoideae (Malvaceae). Methods: We inferred ancestral biomes based on a fossil‐dated molecular phylogeny of 103 species (59% of the clade) and recorded the number of transitions among biomes using biogeographical stochastic mapping based on the dispersal‐extinction‐cladogenesis model. We then estimated diversification rates using state‐specific speciation and extinction rate ( SSE ) methods. Furthermore, we tested the sensitivity of the results to model choice, phylogenetic uncertainty, measurement error and biome definition. Results: We found numerous transitions from evergreen rain forest to seasonally dry biomes, and fewer in the opposite direction. These results were robust to methodological choices. Biome type did not influence diversification rates, although this result was subject to uncertainty, especially related to model choice and biome definition. Main conclusions: Our results contradict the idea of evolutionary biome conservatism in Bombacoideae, and support previous findings that evergreen rain forests serve as a source for the flora of seasonally dry biomes. The impact of biome classification and biome definition on the results suggest caution when using a biome concept for biogeographical reconstruction and diversification rate analysis.